Relações civis e militares entre Brasil e Estados Unidos durante o governo Dutra (1946-1950) : cooperação, resistência, tensões - Zeviani, Rodrigo Udo (2009)
This dissertation aims to analyze the perspective oft he U.S. diplomatic corps on Brazil, both in military as civilian aspects during the government of President Eurico Gaspar Dutra (1946-1950). The political-military elites of Brazil had clearly defined goals at the time aimed at the modernization and development of the country. Thus, these elites knew that to realize his project would require a rapprochement with the U.S.. However, in view of the Cold War in an international context, working with the development of Brazil was not a priority for Americans. We considered the fact that the U.S. government did not want the development of a regional power. The Brazilian elite led development on your project, but had difficulties in fulfilling their pre-established targets. In view of U.S. diplomacy, the project of the Brazilian elite is presented as a greater risk to the hegemony of Brazil than Brazilian left.